A soberania possível: a reconstrução da soberania do povo na modernidade periférica - Ferreira, Desirée Cavalcante (2016)
The objective of this study is to analyze the development of popular sovereignty concept and its compatibility with the brazilian democratic context, taking into consideration interpretations about the particular tensions and issues of its socio-political development. The main purpose is to identify a rational and democratic interpretation of sovereignty, which provides stability and security to juridical relations, but, at the same time, does not ignore demands and obstacles from realities of social exclusion. For this, it will be discussed the need of recognizing the plurality and the impossibility of unification or homogenization of various elements of social life and the insufficiency to use the sovereignty concept on a rhetoric/ideological way to explain the Democratic State foundation.